Rheumatic mitral valve surgery: about 1025 cases - Amellal, M.; Mermad, L.; Moughil, S.; Bjijou, Y.; Bouchikhi, El (International Surgery Journal, 2017)
Background: Rheumatic mitral valvulopathy is often associated with other valvulopathies. It remains endemic in developing countries where it is the leading cause of heart failure and cardiovascular death. Methods: This study provides a retrospective analysis of 1025 cases involving patients who underwent mitral valve surgery at Ibn Sina Hospital in Rabat, Morocco between the dates of January 2, 2001 and April 5, 2012. Preoperatively a clinical and paraclinical assessment has been established. Results: The predominant valvular defects are mitral stenosis, functional tricuspid insufficiency. The gesture was a first intervention in 93% of the cases, with mitral valve replacement in 90% of cases and plasty in 10% of the cases. Conclusions: These patients deserve more accurate evaluation in the choice of the surgical strategy which strongly impacts the post-operative outcomes. This report discusses the factors supporting mitral repair surgery in rheumatic disease, according to the patients' characteristics and the effectiveness of the current repair techniques compared to prosthetic valve replacement in developing countries.